Effects of dietary Docosahexaenoic, training and acute exercise on lipid mediators - Capo, X.; Martorell, M.; Sureda, A.; Tur, J.; Pons, A. (Journal of the International Society of Sports Nutrition, 2016)
Background: Eicosanoids mediate initiation and resolution of inflammation. Our aim was evaluating the effects of training, exercise and docosahexaenoic (DHA) supplementation on plasma eicosanoids levels and peripheral blood mononuclear cells (PBMCs) eicosanoids production.